Anatomical topology of extrahippocampal projections from dorsoventral CA pyramidal neurons in mice - Lee, Junseop; Park, Jeongrak; Jeong, Minseok; Oh, Seo-Jin; Yoon, Jong-Hyuk; Oh, Yong-Seok (Frontiers in Neuroanatomy, 2024)
The hippocampus primarily functions through a canonical trisynaptic circuit, comprised of dentate granule cells and CA1-CA3 pyramidal neurons (PNs), which exhibit significant heterogeneity along the dorsoventral axis. Among these, CA PNs are known to project beyond the hippocampus into various limbic areas, critically influencing cognitive and affective behaviors. Despite accumulating evidence of these extrahippocampal projections, the specific topological patterns—particularly variations among CA PN types and between their dorsal and ventral subpopulations within each type—remain to be fully elucidated. In this study, we utilized cell type-specific Cre mice injected with fluorescent protein-expressing AAVs to label each CA PN type distinctly. This method further enabled the dual-fluorescence labeling of dorsal and ventral subpopulations using EGFP and tdTomato, respectively, allowing a comprehensive comparison of their axonal projections in an animal. Our findings demonstrate that CA1 PNs predominantly form unilateral projections to the frontal cortex (PFC), amygdala (Amy), nucleus accumbens (NAc), and lateral septum (LS), unlike CA2 and CA3 PNs making bilateral innervation to the LS only. Moreover, the innervation patterns especially within LS subfields differ according to the CA PN type and their location along the dorsoventral axis of the hippocampus. This detailed topographical mapping provides the neuroanatomical basis of the underlying functional distinctions among CA PN types.